Edukasi pengetahuan Deteksi Dini Kanker Rongga Mulut pada Masyarakat di Lingkungan RPTRA Harapan Mulia Kemayoran Jakarta Pusat - Audiawati Audiawati; M Zakki; Umi Susana (Info Abdi Cendekia, 2020)
Health problems often arise in the community unnoticed and known causes. This happens because of the low public knowledge about health in the community. These health problems that often arise include high rates of pain including in the oral cavity. Optimal oral health is a balance between physical factors, emotional factors, and social factors. One of them that is quite widely found to occur is oral cancer. Oral cancer is one of the most common cancers worldwide with a higher incidence rate in men than women. Based on RISKESDAS in 2013 showed the prevalence of cancer in Indonesia is increasing over the age and the highest prevalence is at the age of ≥75 years. Abnormalities and deaths caused by oral cancer are still high. Some of the reasons raised are mainly due to the lack of early detection and identification in high-risk groups, as well as the failure to control primary lesions and cervical lymph node metastases, for which early detection is necessary. Community service activities organized are also related to government programs, namely PHBS programme in the Family Order through Health Promotion activities. The purpose of this community service activity is also to increase public awareness of the importance of behaving clean and healthy in the family order that can be started teaching through the provision of oral health education. The method of community service activities carried out is health counseling to the community via online session.